Unintended consequences in transitional justice : social recovery at the local level - Abe, Toshihiro (Lynne Rienner Publishers, Inc., 2018)
Though transitional justice has been hailed by many as the best path toward reconciliation and stability in postconflict and democratizing societies, criticisms of the approach also abound, with a significant number of TJ programs labeled failures. What accounts for this difference of opinion? How is success measured? Have the societies that sought to implement a plan for TJ followed the trajectory laid out in the policy design phase? And if not, was success sometimes achieved despite this variation--or perhaps because of it? Toshihiro Abe addresses these questions through an exploration of TJ.